All the work's a stage: exploring the perceived theatricality of organisational working life. (2017) - Hunt, Nigel; Pronk, Florie Rosalie
Much is known about roles at work. Following role theory, concepts such as role conflict, role overload and role ambiguity are crucial constructs, but where a dramaturgical metaphor is considered meaningful across disciplines including sociology and social psychology, little attention has been paid to theatricality within organisational psychology. This study aims to consider whether and how role theory may be extended by the inclusion of a dramaturgical metaphor at work. How would employees consider their work roles, supposing that work were a stage? Semi-structured interviews and diaries from a sample of 13 employees suggest that the application of a dramaturgical metaphor at work might well equip employees with a powerful work ethic, work repertoire and sense-making device, and therefore deserves further exploration.